The ecology of yew (Taxus baccata) in Ireland - Perrin, Philip Matthew (Trinity College (Dublin, Ireland). Department of Botany, 2003)
This project stemmed primarily from the need for increased ecological knowledge of the development and regeneration of yew communities in Ireland. This was required to make informed management decisions pertaining to the country’s last yew-dominated woodland, Reenadinna Wood, Killamey National Park, as yew woodland is classified as a priority habitat type under Annex I of the EU Habitats Directive. In addition, recent palaeoecological research has suggested that yew woodland may have been a far more important feature of the natural Irish landscape than has been thought hitherto. In view of ongoing initiatives to increase native woodland cover, it is important to understand as fiilly as possible the vegetation composition of this past landscape. Hence, this project was also concerned with elucidating the past distribution of the species and the reasons for its decline.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin